Efek pemberian kombinasi jus aloe vera dan glibenklamid terhadap penurunan kadar glukosa darah pada model tikus diabetes yang diinduksi dengan streptozotosin dan nikotinamid - I Kadek Dwi Iman Muliawan (Intisari Sains Medis, 2019)
Introduction: Antidiabetic oral was not optimal for reducing blood glucose, patients use the various antidiabetic herbs along with antidiabetic drug for controlling their blood glucose level. Aloe vera is one of the plants that are often used by diabetic patients who are also taking antidiabetic medication and susceptible arise interaction between them. Objectives of this study is to determine the effect of Aloe vera juice and glibenclamide combination in reducing blood glucose levels in the diabetic rats model induced by streptozotosin and nicotinamide.Method: Research metodology the diabetic rats were randomized into three groups and administered CMC 0,5%, glibenclamide, or Aloe vera and glibenclamide. The animals were treated orally once daily for twentyeight days. Data were analyzed using one way AnovaResult: Findings of this study indicate that of Aloe vera juice in combination with glibenclamide significantly reduced blood glucose levels significantly in diabetes rats model (p<0,05)Conclusion: Combination of Aloe vera juice and glibenclamide be able to lower blood glucose levels and statistically significant.